Development of Hydroxyapatite-Based Bone Phantoms from Blood Cockle Shells: Effect of Material Composition on X-ray Attenuation - Chika Pricilla Putri Irawan; Devina Rayzy Perwitasari Sutaji Putri; Rahmawati Munir; Zetsaona Sihotang (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
Radiological phantom is a teaching and simulation tool designed to replicate the physical properties and characteristics of human body tissues, primarily for the evaluation of medical imaging. One alternative material for phantom fabrication is the blood cockle shell (Anadara granosa), which contains hydroxyapatite (HA). This study aims to investigate the effect of varying material compositions on the linear attenuation coefficient (μ) of X-rays in bone phantoms, as well as to determine the optimal composition that approximates the reference values of human bone. The research method involved mixing rice bran, resin, and HA powder synthesized from blood cockle shells in varying HA compositions of 20g, 25g, 40g, and 50g. Each phantom was then scanned using  a CT scanner to obtain CT Number values, which represent the linear attenuation coefficient (μ) values. The results showed that the correlation between composition and μ value was not entirely linear, due to the uneven distribution of HA and the presence of voids within the phantom structure. Among the four samples, the phantom with 40 grams of HA (Phantom 3) demonstrated the closest approximation to cortical bone characteristics, with an average CT Number of 1102.15 HU and a μ value of 0.441 cm⁻¹, approximating the attenuation coefficient of human cortical bone. These findings highlight the potential use of waste materials such as blood cockle shells as a main material for bone phantoms that can closely mimic human bone properties.